Helper Syndrome and Pathological Altruism in nurses – a study in times of the COVID-19 pandemic - Maringgele, Victoria E.; Scherr, Martin; Aichhorn, Wolfgang; Kaiser, Andreas K. (Frontiers in Psychology, 2023)
Background: Pathological Altruism and the concept of Helper Syndrome are comparable. We focused on Schmidbauer's description because it provides a comprehensive and testable definition. Nevertheless, this concept of Helper Syndrome has not yet been empirically investigated in a sample of helping professionals. Aim: To investigate whether nurses working with covid-19 patients are more likely to have Helper Syndrome compared with individuals from non-helper professions. Methods: The online survey took place between April 2021 and February 2022, in urban and rural regions of Salzburg, during the time of the COVID-19 pandemic. Nurses (n = 447) and controls (n = 295) were compared regarding Helper Syndrome characteristics. To measure characteristics of Helper Syndrome the following questionnaires were used: WHO-Five (WHO-5), selected scales of the Personality, Style and Disorder Inventory (PSSI) and the Freiburg Personality Inventory-Revised (FPI-R), the Alcohol Use Disorders Identification Test (AUDIT). Insecure gender identity and self- assessment of having a Helper Syndrome was measured by a Likert scale. Results: In both groups, Helper Syndrome was detected (nurses 29.5 %, controls 30.5 %). Participants with Helper Syndrome showed significant differences in personality styles and traits, namely significantly higher scores for Foreboding-Schizotypical Personality Style, Spontaneous-Borderline Personality Style, Amiable-Histrionic Personality Style, Ambitious-Narcissistic Personality Style, Loyal-Dependent Personality Style, Helpful-Selfless Personality Style, Carefully-Obsessive Personality Style, Optimistic-Rhapsodic Personality Style, Social Orientation, Strain, Emotionality and lower well-being. The only difference between nurses and controls was that nurses were significantly less open aggressive. Conclusions: For the first time, we were able to demonstrate Schmidbauer's concept of Helper Syndrome. According to our data, we found a subgroup of individuals similar to Schmidbauer’s description of Helper Syndrome, but this sample was independent of helping or non-helping profession. These individuals seem to be at higher risk for psychiatric disorders.